1994
DOI: 10.2172/211385
|View full text |Cite
|
Sign up to set email alerts
|

Total System Performance Assessment, 1993: An evaluation of the potential Yucca Mountain repository, B00000000-01717-2200-00099, Rev. 01

Abstract: Total System Performance Assessments are an important component in the evaluation of the suitability of Yucca Mountain, Nevada as a potential site for a mined geologic repository for the permanent disposal of high-level radioactive wastes in the United States. The Total System Performance Assessments are conducted iteratively during site characterization to identify issues which should be addressed by the characterization and design activities as well as providing input to regulatoryAicensing and programmatic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

1997
1997
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 11 publications
(21 reference statements)
0
9
0
Order By: Relevance
“…For the most part, these analyses as documented in previous total system 6-22 performance assessment iterations in (Barnard et al, 1992Eslinger et al, 1993;Andrews et al, 1994;Wilson et al, 1994;CRWMS M&O, 1995a) have identified the key conceptual models and parameters that significantly affect the predictions of postclosure performance. The results, conclusions and recommendations of these previous total system performance assessment analyses (as well as other performance assessment analyses of individual components of the overall system, such as the geosphere performance as exemplified in the ground-water travel time analyses and the engineered barrier performance as embodied in analyses of releases from the engineered barrier system) have been used to shape the present waste containment and isolation strategy.…”
Section: Performance Allocation and Hvpothesis Testingmentioning
confidence: 99%
See 4 more Smart Citations
“…For the most part, these analyses as documented in previous total system 6-22 performance assessment iterations in (Barnard et al, 1992Eslinger et al, 1993;Andrews et al, 1994;Wilson et al, 1994;CRWMS M&O, 1995a) have identified the key conceptual models and parameters that significantly affect the predictions of postclosure performance. The results, conclusions and recommendations of these previous total system performance assessment analyses (as well as other performance assessment analyses of individual components of the overall system, such as the geosphere performance as exemplified in the ground-water travel time analyses and the engineered barrier performance as embodied in analyses of releases from the engineered barrier system) have been used to shape the present waste containment and isolation strategy.…”
Section: Performance Allocation and Hvpothesis Testingmentioning
confidence: 99%
“…In all instances in which the fracture flow percentage was markedly increased from the nominal values in Total System Performance Assessment -1993 (Andrews et al, 1994;Wilson et al, 1994) or Total System Performance Assessment -1995 (CRWMS M&O, 1995a), the increased fracture flux resulted in reduced travel times through the unsaturated zone and therefore an increased likelihood of obtaining significant releases and doses at the accessible environment boundary in the first 10,000 years after repository closure. These results reemphasize the need to focus the site characterization program on ascertaining the distribution and magnitude of localized fracture flow in the repository block.…”
Section: -24mentioning
confidence: 99%
See 3 more Smart Citations